Investigation on Physical and Optical of Praseodymium Doped Sodium Aluminium Barium Phosphate Glasses. (January 2020) - Sangwaranatee, N. W.; Kiwsakunkran, N; Kaewkhao, J
Abstract: Sodium aluminium barium phosphate glasses doped with different concentration of Pr2 O3 were synthesized by melt quench technique. These glasses were varied concentrations of Pr2 O3 at 0, 0.05, 0.10, 0.50, 1.00 and 2.00 mol%. Their physical properties like density (ρ) and refractive index ( n ) were measured at room temperature. Also, optical absorption and photoluminescence spectra of these glasses have been acquired at room temperature. It was found that the intensity were increase with increasing concentration of Pr2 O3 . UV-Vis and NIR (250-2500 nm) spectra have been measured for all studied glass samples and discussed. The photoluminescence spectra recorded under 445 nm excitation exhibited the emission bands at 528, 598 and 639 nm corresponding to the emission transitions 3 P1 → 3 H5, 1 D2 → 3 H4, and 3 P0 → 3 F2 respectively. The Judd-Ofelt (JO) parameters Ωλ (λ = 2, 4 and 6) have been calculated to explore the bonding environment around the Pr 3 + ions. The CIE chromacity color coordinates (x, y) are calculated from the emission spectra which indicates the located in the yellow-orange region. The prepared glasses are potential candidates for laser applications.